The Role of Operationally Distinct Options in Supporting Joint Human-Automation Planning. (September 2016) - Depass, Beth; Roth, Emilie; Scott, Ronald; Harter, Jonathan; Wampler, Jeffrey
We describe a prototype cognitive work aid for airlift mission allocation and scheduling. A key design challenge was how to generate and visualize multiple operationally distinct options to broaden the set of alternative plans that Mission Planners consider, increasing overall efficiency and effectiveness of the mission planning organization. We first describe the distributed nature of the mission planning domain, where key considerations arise across different organizational boundaries, come in over time and dynamically change. We describe techniques we developed for generating and displaying multiple operationally distinct mission planning solutions, to facilitate contingency planning and collaboration across organizatinal boundaries. This work is part of a longer term program to develop and demonstrate concrete techniques for more effective joint cognitive systems.